Soft Palate Dysfunction in Children With Microtia. Issue 1 (January 2019) - van Hövell tot Westerflier, Claire; Bracamontes, Ignacio Colin; Tahiri, Youssef; Breugem, Corstiaan; Reinisch, John
Abstract : Background: Speech issues in microtia patients have been historically attributed to poor hearing. However, the authors have noted that almost all patients with microtia have palatal dysfunction. The aim of this study is to determine the prevalence of soft palate dysfunction (SPD) and velopharyngeal insufficiency (VPI) in microtia patients. Methods: A prospective cohort study was performed on consecutive microtia patients from March to June 2017. Clinical characteristics were collected. Palate movement was rated by oral examination and degree of nasal escape by the mirror-fogging test. Correlations between clinical characteristics of microtia and SPD were determined. Results: Ninety-seven (40 unilateral, 27 bilateral, and 30 control) children met inclusion criteria. Among all 67 patients with microtia, 96% (64 patients) showed SPD. Twenty-four unilaterals (60%) and 23 bilaterals (85%) had observable VPI by mirror examination. Of these patients, nasality was noticeable to the examiners in 14 unilaterals (58%) and 21 bilaterals (91%). Sixteen of the 27 bilaterals (59%) showed almost no movement of the soft palate. There was a significant correlation between SPD and mirror-fogging. A less developed middle ear as determined by computed tomography scan was associated with palatal dysfunction ( P = 0.007). The severity of mandibular shift ( P = 0.048) and presence of a syndrome ( P = 0.045) were associated with grade of VPI. The severity of the ear deformity ( P = 0.007) and presence of a syndrome ( P = 0.034) were also correlated with the presence of SPD. Conclusions: This is the first study that documents the presence of VPI due to soft palate dysfunction in patients with isolated and nonisolated microtia. Abstract : Supplemental Digital Content is available in the text